Whether Hematological Parameters are Predictor of Pregnancy Induced Hypertension (Medical Forum Monthly, 2024)
Objective: To find role of hematological parameters in predicting hypertension in pregnant women.Study Design: Case control study.Place and Duration of Study: Department of Gynecology and Obstetrics, Nishtar Hospital Multan from October 2017 to January 2018.Materials and Methods: The sample size of this study was 125 patients. They were divided in three groups as 60 patients in pre-eclamptic group, 20 patients in severely pre-eclamptic and 45 pregnant women in control group. . One way ANOVA was used to calculate mean and standard deviation of given data. In all the statistical calculation, the p value of <0.05 was considered to be significant. Results: A total number of 125 patients were included in this study. All the pregnant women were divided into three groups. 48% (n=60) pregnant women were in pre-eclamptic group, 16% (n= 20) women in severe pre-eclamptic group and 36% (n=45) pregnant women were in control group. In pre-eclamptic group, the mean cell value, mean cell Haemoglobin, mean cell Haemoglobin concentration, RBC distribution width, mean platelet value and MPV / platelet count was 82.62±4.99, 27.52±2.68, 34.12±1.85,14.22±2.30, 225.96±36.50, 8.9±1.03 and 0.0415±0.018 respectively. In severe pre-eclamptic group, the mean cell value, mean cell Haemoglobin, mean cell Haemoglobin concentration, RBC distribution width, mean platelet value and MPV / platelet count was 83.67±9.43, 29.63±2.81,34.20±0.83,15.02±2.89, 9.15±1.23 and 0.0481±0.010 respectively. When pre-eclamptic and severely pre-eclamptic patients were compared with control group, the difference was statistically insignificant according to CBC, platelet count, and MPV.Conclusion: From this study, we have concluded that hematological parameters like CBC, platelet count and mean platelet volume (MPV) values are not predictor of pregnancy induced hypertension.